2015
DOI: 10.1007/s12192-015-0613-0
|View full text |Cite
|
Sign up to set email alerts
|

Crocin and Quercetin protect HCT116 and HEK293 cells from Zearalenone-induced apoptosis by reducing endoplasmic reticulum stress

Abstract: Mycotoxins are considered to be significant contaminants of food and animal feed. Zearalenone (ZEN) is a non-steroidal estrogenic mycotoxin produced by several species of Fusarium in cereals and agricultural products. ZEN has been shown to be cytotoxic, genotoxic, and mutagenic in different cell types. In the present study, we investigated the involvement of endoplasmic reticulum (ER) stress in ZENmediated toxicity in human intestine (HCT116) and kidney (HEK293) cells and evaluated the effects of the two commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 62 publications
4
47
0
2
Order By: Relevance
“…Transcriptional activation of CHOP plays an important role in ER stress-induced apoptosis in cells [34]. Furthermore, a prior study reported similar data in human colon HCT116 cells and human kidney HEK293 cells [35]. In this cell culture study, ZEN induced ER stress and ER stress-mediated cell death through the CHOP pathway.…”
Section: Discussionsupporting
confidence: 74%
“…Transcriptional activation of CHOP plays an important role in ER stress-induced apoptosis in cells [34]. Furthermore, a prior study reported similar data in human colon HCT116 cells and human kidney HEK293 cells [35]. In this cell culture study, ZEN induced ER stress and ER stress-mediated cell death through the CHOP pathway.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that the ER stress pathway has been reported to participate in oxidative damage and apoptosis induced by ZEN 22 24 , 46 . To provide further evidence that the A2 fermentation broth exerts a protective effect from ZEN-induced kidney injury, we explored whether the A2 fermentation broth could decrease both ER stress and apoptosis induced by ZEN.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ZEN could alter the enzymatic and hematological parameters of mice, and it could induce higher levels of oxidative stress 19 21 . Meanwhile, ZEN-induced apoptosis is characterized by ROS production and increased lipid peroxidation 22 , 23 . A previous study demonstrated that ZEN induced apoptosis in RAW 264.7 macrophages through endoplasmic reticulum stress (ER stress) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Lipoic acid and vitamin C were evaluated in vivo in terms of their abilities to alleviate the liver oxidative damage induced by AFB1 or ZEA, and vitamin C was found to alleviate the damage via regulating the nuclear receptor signaling pathway with changes of nuclear receptor genes (PXR, constitutive active receptor [CAR]) (Ma et al., ; Shi et al., ). Crocin with a high antioxidant capacity was found to protect HEK293 cells and human colon carcinoma (HCT116) cells against apoptosis and endoplasmic reticulum stress induced by ZEA and its 2 metabolites (Ben Salem et al., , ). Carotenoids such as lycopene were found to exhibit protection against ZEA‐induced oxidative stress, inflammatory and reproductive damages, and OTA‐induced DNA damage in male mice (Aydin et al., ; Boeira et al., ).…”
Section: Food Compounds Especially Those Of Plant Origin For Prevenmentioning
confidence: 99%